The Need to Engage with African Experiences in the United Nations Sanctioning Process: A Case Study of the Central African Republic - Sharma, Vishal (Comparative and International Law Journal of Southern Africa)
The United Nations (UN) can impose sanctions by means of regional and other arrangements. History has demonstrated that during the Cold War era in Europe, the UN has imposed fewer sanctions than in the post-Cold War era. Although the UN Charter originally did not provide for the use of sanctions to protect democracy, it did protect international peace and security. However, the UN Security Council (UNSC) and other regional arrangements and communities like the EU and the AU are currently imposing sanctions even on undemocratic regime change, which should be an internal matter of a state. This development shows increased international commitment in favour of democracy. Further, the UNSC and the EU use different approaches than the AU, when removing sanctions. The AU’s approach in removing sanctions is more realistic and pragmatic. A case study of the Central African Republic shows that the UNSC and the EU approaches on sanctions towards African states could be counter-productive. It is advisable that the UNSC should consider African perspectives, by taking AU opinion into account, when imposing, modifying, or removing sanctions on the African continent. It would further increase local acceptance of sanctions, rendering them more effective. It is necessary to understand that problems in African states could have had local origins, but external factors such as international business interests could have aggravated these problems. Therefore, the targeted and smart sanctions will be more effective if international business interests, that help rebels, are also included in sanctions.